From Shtetl to Stardom Jews and Hollywood - Renov, Michael (Jewish Role in American Life: An Annual Review, 2016)
The outsized influence of Jews in American entertainment from the early days of Hollywood to the present has proved an endlessly fascinating and controversial topic, for Jews and non-Jews alike. From Shtetl to Stardom: Jews and Hollywood takes an exciting and innovative approach to this rich and complex material. Exploring the subject from a scholarly perspective as well as up close and personal, the book combines historical and theoretical analysis by leading academics in the field with inside information from prominent entertainment professionals. Essays range from Vincent Brook's survey of the stubbornly persistent canard of Jewish industry "control" to Lawrence Baron and Joel Rosenberg's panel presentations on the recent brouhaha over Ben Urwand's book alleging collaboration between Hollywood and Hitler. Case studies by Howard Rodman and Joshua Louis Moss examine a key Coen brothers' film A Serious Man (Rodman) and Jill Soloway's groundbreaking television series Transparent (Moss).